(untitled) (Elmergib Journal of Human Sciences, 2025)
Instructional poetry is one of the methods used by scholars to preserve knowledge, facilitate it, and make it accessible to learners. Through it, knowledge has been preserved, and through it, people have learned about religious and worldly matters. It presents knowledge in a simple, accessible manner that is deeply embedded in the mind and easily recalled whenever required. This is because people love poetry, are drawn to it, and take pride in memorizing it and citing it. From this standpoint, this paper titled (Educational Poetry of Sheikh Muhammad Muftah Qaryu, the System of Grammatical Truths as a Model) aims to unveil a master of this art. He is one of its prominent figures, and his life, teachers, and students are presented, clarifying his methodology in the systems. Before this, a brief overview of the meaning of educational poetr.